Inclusive Education Definitions and Practices: Exploring Perspectives of Education Professionals in Mexico City. Issue 1 (20th July 2020) - Francis, Grace Lavín; Lavin, Carlos E.; Sanchez, Jessica; Reed, Alexandra S.; Mason, Linda
Abstract: Inclusive education (IE) is globally recognized as instrumental in facilitating equity and quality education for all students. However, despite literature documenting positive outcomes associated with IE, IE definitions and strategies vary and are not well researched in countries such as Mexico that are in the early stages of adopting IE policies. Therefore, the purpose of this study was to examine how professionals working at schools that identified themselves as "inclusive" in Mexico City, Mexico defined IE and implemented IE. Findings indicated that participants defined or described IE in several ways, including physical and educational access, socialization, personal development, equality among students, and a paradigm that requires constant reflection. Participants also described numerous IE strategies related to school culture, high expectations, administrative support, professional development, collaboration, student evaluation, accommodations and modifications, paraprofessional support, and parent involvement. Implications for practice and future research are discussed.